The factors Affecting to amount of Fixed Deposit Accounts of Banque Pour Le Commerce Exterieur Lao Public (BCEL) - SONEVANHNACHANPING, Phoummachan; CHANTHAVONE, Thongphanh; PHOUNNALY, Phayvanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The Social economic development of Lao PDR is to help Lao people have a better lives and it’s very important and necessary to have fund for investment on the other activities, due to Lao PDR is the least developed country, almost of population in the country have low income and the total amount of saving in the country are not enough, the main income generation of the people is only for their consumption and to serve their family, So the main fund for the least develop country are from abroad and some are from the country itself. A using fund from abroad is depending on growing of economic development ratio and the interest rate changing, so the source of fund of the country is only saving and Laos PDR doesn’t have enough saving for release for the credit providing or invest in the economic site. A study of the factors Affecting to amount of Fixed Deposit Accounts of Banque Pour Le Commerce Exterieur Lao Public(BCEL), which provides quantitative analysis and uses secondary data annually from the first quarter of year 2012 to the third of year 2019 by testing the relationship of the factors Affecting to amount Fixed Deposit Accounts of Banque Pour Le Commerce Exterieur Lao Public(BCEL) by the Ordinary Least Squares(OLS) methodology for making a choice of saving and investment which will be a great affective to develop the country by credit providing of Banque Pour Le Commerce Exterieur Lao Public(BCEL) The result of the study found that the fix deposit structure of BCEL’s clients are almost from Lao currency by average 62.35% and they have long term deposit for earning money from the interest, for their retirement and deposit for their children, aside from that, the interest changing is affecting to the amount of fix deposit in the opposite way, when we have analyzed of the factors affecting to amount of Fixed Deposit Accounts of BCEL are cause from the interest rate of 3 month of fix deposit, the changing of the total assets of BCEL and the ratio of the Lao Securities Exchange, but increasing of braches and unit service of the BCEL, the interest of Laos government banknote and inflation are not affected to the amount of fix deposit of BCEL and these factors are statistically significance at 95% level of confidence.